EVALUASI KESESUAIAN LAHAN UNTUK BUDIDAYA TANAMAN SEMANGKA (STUDI KASUS DI KECAMATAN TUAH MADANI, KOTA PEKANBARU) - Sukma, Dinda Razita; Gusmawartati; Idwar; Nasrul, Besri; Umami, Irwin Mirza (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Evaluation of land suitability is carried out to perceive the potential and limitation factors of an area as an agricultural development area. Air Putih Village is one of the potential area for watermelon development area. This research was conducted to perceive the level of actual and potential land suitability for watermelon cultivation in Air Putih Village, Tuah Madani District, Pekanbaru City in the form of a semi-detailed map scale of 1:25.000. The method used in this study was a purposive sampling survey based on a map of land units. There were 7 units of land covering an area of 330.56 ha with a total of 21 sample points. Data were sourced from field observation, analysis of chemistry and physics of soil samples at the laboratory and secondary data from climate data. Land suitability assessment was carried out using the limiting factor matching method. The actual land suitability was in class S3 and N with effective soil depth (rc), base saturation (nr), slope (eh) and soil texture (rc) as limiting factors. The class of the potential land suitability for watermelon cultivation were S2, S3 and N.